Extracellular aminopeptidase modulates biofilm development of Pseudomonas aeruginosa by affecting matrix exopolysaccharide and bacterial cell death. Issue 5 (24th September 2018) - Zhao, Tianhu; Zhang, Yuhuan; Wu, Huijun; Wang, Di; Chen, Yihua; Zhu, Mei‐Jun; Ma, Luyan Z.
Summary: Biofilm bacteria are embedded within a self‐secreted extracellular matrix that contains a considerable amount of proteins including many extracellular enzymes. However, little is known about the roles of such enzymes in biofilm development. Here, we studied P seudomonasa eruginosa a minop eptidase (PaAP, encoded by PA2939 that we named the gene as paaP in this study), a quorum‐sensing‐regulated enzyme and one of the most abundant extracellular proteins in the biofilm matrix of this opportunistic pathogen and environmental bacterium. We found that deletion of paaP in P. aeruginosa increased initial attachment and biofilm formation at early stages of biofilm development. After 24 h growth, loss of PaAP resulted in substantial cell death and biofilm disruption. Bacterial cell death was independent of biofilm matrix polysaccharide Psl, while biofilm disruption was due to the degradation of Psl matrix by dead‐bacteria‐released glycosyl hydrolase PslG, thereby leading to biofilm dispersion. PaAP functioned extracellularly and aminopeptidase catalytic activity was essential for its effect on biofilm development. Our data reveal an important role of extracellular aminopeptidase in biofilm development, suggesting PaAP as a therapeutic target for preventing P. aeruginosa infection and combating biofilm‐related complications.